High‐performance In–Zn–O thin‐film transistors with a soluble processed ZrO2 gate insulator. Issue 7 (12th June 2013) - Son, Byeong‐Geun; Je, So Yeon; Kim, Hyo Jin; Lee, Chul‐Kyu; Lee, Chang‐Kyu; Hwang, Ah Young; Won, Ju Yeon; Song, Ji Hun; Choi, Rino; Jeong, Jae Kyeong
Abstract Spin‐coated zirconium oxide films were used as a gate dielectric for low‐voltage, high performance indium zinc oxide (IZO) thin‐film transistors (TFTs). The ZrO2 films annealed at 400 °C showed a low gate leakage current density of 2 × 10–8 A/cm2 at an electric field of 2 MV/cm. This was attributed to the low impurity content and high crystalline quality. Therefore, the IZO TFTs with a soluble ZrO2 gate insulator exhibited a high field effect mobility of 23.4 cm2/V s, excellent subthreshold gate swing of 70 mV/decade and a reasonable Ion/off ratio of ∼106. These TFTs operated at low voltages (∼3.0 V) and showed high drain current drive capability, enabling oxide TFTs with a soluble processed high‐k dielectric for use in backplane electronics for low‐power mobile display applications. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)